2017
DOI: 10.5812/archneurosci.14332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saffron (Crocus Satious L.) as an Add-On Therapy to Sertraline in Mild to Moderate Generalized Anxiety Disorder: A Double Blind Randomized Controlled Trial

Abstract: Background: Generalized anxiety disorder (GAD) is known as the most prevalent anxiety disorder. Saffron has been previously approved as an effective adjuvant therapy in depression and might alleviate GAD symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…and (c) studies that evaluated the effect of saffron in combination with other foods and supplements (n = 2). Fourteen articles (18 arms) representing 788 participants (Abedimanesh et al, 2017;Azimi, Ghiasvand, Feizi, Hariri, & Abbasi, 2014;Fadai et al, 2014;Gout et al, 2010;Jafarnia et al, 2017;Javandoost et al, 2017;Kermani, Kazemi, et al, 2017;Kermani, Zebarjadi, et al, 2017;Mansoori et al, 2011;Milajerdi et al, 2018;Modaghegh, Shahabian, Esmaeili, Rajbai, & Hosseinzadeh, 2008;Mohamadpour, Ayati, Parizadeh, Rajbai, & Hosseinzadeh, 2013;Nikbakht-Jam et al, 2016;Sepahi et al, 2018) met our inclusion criteria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…and (c) studies that evaluated the effect of saffron in combination with other foods and supplements (n = 2). Fourteen articles (18 arms) representing 788 participants (Abedimanesh et al, 2017;Azimi, Ghiasvand, Feizi, Hariri, & Abbasi, 2014;Fadai et al, 2014;Gout et al, 2010;Jafarnia et al, 2017;Javandoost et al, 2017;Kermani, Kazemi, et al, 2017;Kermani, Zebarjadi, et al, 2017;Mansoori et al, 2011;Milajerdi et al, 2018;Modaghegh, Shahabian, Esmaeili, Rajbai, & Hosseinzadeh, 2008;Mohamadpour, Ayati, Parizadeh, Rajbai, & Hosseinzadeh, 2013;Nikbakht-Jam et al, 2016;Sepahi et al, 2018) met our inclusion criteria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The range for the doses of saffron administered in studies included in this review was 5 to 1,000 mg/day, and no major adverse events or toxic reactions were reported. None of the studies included in this review provided further information on the safety profile of saffron or crocin to aid their use as a clinical therapeutic agent (Abedimanesh et al, 2017;Azimi et al, 2014;Fadai et al, 2014;Gout et al, 2010;Jafarnia et al, 2017;Javandoost et al, 2017;Kermani, Kazemi, et al, 2017;Kermani, Zebarjadi, et al, 2017;Mansoori et al, 2011;Milajerdi et al, 2018;Modaghegh et al, 2008;Mohamadpour et al, 2013;Nikbakht-Jam et al, 2016;Sepahi et al, 2018). The quality of the evidence identified limits recommendation of saffron for clinical management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations